2013
DOI: 10.1080/09603123.2013.773586
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte DNA damage in Turkish asphalt workers detected by the comet assay

Abstract: Asphalt has a highly complex structure and it contains several organic compounds including polycyclic aromatic hydrocarbons and heterocyclic compounds. In this study, comet assay was used to detect the DNA damage in blood lymphocytes of 30 workers exposed to asphalt fumes and 30 nonexposed controls. This is the first report on Turkish asphalt workers' investigated DNA damage using the alkaline single cell gel electrophoresis (SCGE). The DNA damage was evaluated by the percentage of DNA in the comet tail (% tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…In this assay, the level of DNA damage in the population studied was <4% (tail). This type of identification of damage to genetic material has previously been used to evaluate exposure to environmental or occupational factors, and for diagnosis of cancer or diseases resulting from impaired DNA repair mechanisms (Gedik et al 1992;Jophnson and Ferris 2005;Bacaksiz et al 2014). It has also found application in assessing the quality of semen in animals (Fraser and Strzeżek 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In this assay, the level of DNA damage in the population studied was <4% (tail). This type of identification of damage to genetic material has previously been used to evaluate exposure to environmental or occupational factors, and for diagnosis of cancer or diseases resulting from impaired DNA repair mechanisms (Gedik et al 1992;Jophnson and Ferris 2005;Bacaksiz et al 2014). It has also found application in assessing the quality of semen in animals (Fraser and Strzeżek 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its wide variety of applications, comet assay is utilized by many researchers to assess DNA damage in the workers of different industries. During the literature review, a number of health biomonitoring studies were found that used comet assay (12)(13)(14)(15)(16). Those studies were aimed at assessing the amount of genotoxicity caused by particular exposures in the workers of different industries, such as open-cast coal mining (17), the automotive industry (18), lead battery recycling plants (19), and the petrol industry (20).…”
Section: Resultsmentioning
confidence: 99%
“…Comet assay could be recognized as an excellent marker and a supplementary technique for monitoring the presence or absence of genotoxic effects. Another study used comet assay to detect DNA damage in the blood lymphocytes of 30 workers exposed to asphalt fumes and 30 non-exposed controls (15). DNA damage was evaluated by the percentage of the DNA present in the comet tail (% tail DNA) in each cell.…”
Section: Resultsmentioning
confidence: 99%
“…This instability generates further mutations, which may lead to developmental abnormalities, embryo death, reproductive disorders, and cause neoplastic transformation (Ashby, Tinwell, Lefevre, & Browne, 1995;Wójcik, Andraszek, Ciszewska, & Smalec, 2013). The comet assay is a sensitive test used to measure DNA damage and repair in single cells (Ashby et al, 1995 (Bacaksiz, Kayaalti, Soylemez, Tutkun, & Solemezoglu, 2014;Gedik, Ewen, & Collins, 1992). In animals, it was used to evaluate semen quality in the boar (Fraser, Parda, Filipowicz, & Strzeżek, 2010) and chinchilla (Niedbała et al, 2015), and to assess chromatin instability in the somatic cells of sheep (Wójcik et al, 2018).…”
Section: Discussionmentioning
confidence: 99%